Arboreal City-States: Phyto-Warfare in Urarina Metropolitan View - Fabiano, Emanuele (Cadernos de Campo (São Paulo, 1991), 2023)
In the Urarina’s urban imaginary, an extensive network of metropolises occupies the rainforest. These “dendritic cities” have strongly normative and even oppressive features, inspired by hierarchical and authoritarian socio-political models, which define the relationship between the different tree species and their “human neighbors.” Production, technology, and trade guide the governments of these huge city-states, places noted for their productivity and efficiency, in which intensive cultivation, large-scale cattle ranching, and the manufacture of industrial artifacts sustain a widespread “phyto-war policy.” My paper analyze how the topography and the social morphology of these city-states reproduce, in a cosmological plane, the forms of domination and subordination experienced today by the Urarina in northern Peru. In addition, I discuss how the production –and constant updating– of this indigenous urban imaginary serves to “denaturalize” the effects deriving from closer relations with the stratified and technological national society.